Student mobility and differentiated access to Spanish citizenship: the case of Mexicans, Colombians and Brazilians in Galicia - Alma Paola Trejo Peña; Jakson Renner Rodrigues Soares (FahrenHouse, 2017)
Tertiary level enrollment and student mobility is increasing worldwide. As a result, universities are open to receive foreign students, and specifically the Spanish Higher Education Institutions are working to attract some of that international mobility. In recent years, Latin American students are the main applicants for study permits in Spain. Among them, Brazilians, Mexicans and Colombians are the most numerous requestors in the Spanish educational system. On the other hand, access to Spanish citizenship depends on several factors, and one of the most important ones is having legally lived in Spain for a minimum period. This paper presents a relationship between the temporary mobility for study and the achievement of Spanish citizenship by Mexicans, Colombians and Brazilians. This research was conducted using the documentary approach, since this technique allows transforming primary documents on an analytical representation of the addressed phenomenon (Oliveira, 2007). The results show that in Galicia, in the case of Brazilians and Colombians, having a migration project could lead to the Spanish nationality, while for Mexicans, other factors limit this possibility. Furthermore, the experience in the host country, previous experiences and hospitality are variables that interfere in this process.